CYTOTOXIC ACTIVITY OF TAXUS SUMATRANA (MIQ.) DE LAUB. BARK, LEAVES, AND SHOOTS ON HELA, T47D, AND MCF-7/HER2 CELL LINES - WAHYUNI, FATMA SRI; PUTRI, DESI EKA; PUTRA, YOZARWARDI USAMA; HAMIDI, DACHRIYANUS (International Journal of Applied Pharmaceutics, 2024)
Objective: Taxus sumatrana (Miq.) de Laub. (cemara Sumatra) is one of the plants found in Indonesia and other countries known as a medicine plant. Taxus's bark, leaves, and shoots are used traditionally and massively for some diseases (cancer, etc.), so recently it has become a rare plant. The chemical constituents of T. sumatrana are alkaloids, steroids, tannins, and flavonoids. This study aimed to investigate the potential anticancer properties of T. sumatrana bark, leaves, and shoot extracts. Methods: The cytotoxic activity against the HELA, T47D, and MCF-7/HER2 cell lines was determined using the MTT assay. Each cell was cultured on 96 well plates treated with extract of T. sumatrana with concentrations of 100, 10, 1, and 0,1 µg/ml. Cells were incubated for 48 h at 37 °C, 5% CO2 and then given 100 µl MTT solution 0.5 mg/ml in PBS (Phosphate Buffer Saline) for 4 h. The results of the measurements were processed with the GraphPad Prism Program. Results: The bark, leaves, and shoots extracts have strong cytotoxic activity based on IC50 parameters. The mean IC50 of bark, leaves, and shoots on the HELA cell line consecutively 8.94; 5.93; and 4.08 μg/ml; on the T47D cell line 5.80, 4.86, and 4,11 μg/ml; and on MCF-7/HER2 cell line 7.46, 10.60, and 13.74 μg/ml). Conclusion: T. sumatrana bark, leaves, and shoots have potential anti-cancer properties.